She works hard for the money: Tackling low pay in sectors dominated by women. Evidence from health and social care - Torsten Müller (European Trade Union Institute (ETUI), 2019)
This working paper provides data confirming that workers in lower-skilled health and social care assistant positions earn considerably less than the national average wage in their country. The publication argues that the wage penalty for working in female-dominated sectors and occupations such as health and social care can be explained by the underfinancing and privatisation of social care, weaker bargaining power in these sectors than many male-dominated sectors and the fact that care work is subject to a general undervaluation of what often continues to be seen as "women's" work.
Keywords: 330; female workers; low income; bargaining power; healthcare; Social service; Weibliche Arbeitskräfte; Niedrigeinkommen; Verhandlungsmacht; Gesundheitswesen; Sozialer Dienst